FEC: uma ferramenta estratégica circular para favorecer a tomada de decisão sobre as forças que impactam o mercado de caminhões movidos a biometano - Pereira, Reinalda Blanco (2023)
The research aimed to use a circular strategic tool to favor decision-making concerning the forces that impact the market for trucks powered by biomethane. The novelty of the study is centered on the construction of a tool that helps organizations within a strategic and circular perspective. The constructed instrument presents a criterion that selects the enterprise as a user: the presence of CE (Circular Economy) in its products or services. The tool allows a detailed analysis of the essential areas of the business, with the purpose of identifying the strengths and weaknesses of the enterprise, for subsequent strategic decision-making. The tool is easy to use, with a clear and objective sequence, starting with the external components, following with the internal ones and ending with the environmental ones. The study had three phases, namely: in Phase I, the Circular Business Model to be used in the tool was defined and the Circular Strategic Tool was built; in Phase II, market research was carried out through the application of a questionnaire to 29 entrepreneurs from different branches and sizes of companies, to answer questions about the viability of the constructed instrument, and in Phase III, the application of the multicriteria Analytic Hierarchy Process method was carried out (AHP). A questionnaire was applied to 22 employees at the managerial level of the manufacturing unit of a heavy vehicle industry, and the analysis of the AHP method had the help of Super Decision Software (SDS); and validation of the Circular Strategic Tool was carried out, with the participation of 23 specialists from the academic area and six businessmen. Cronbach's Alpha Coefficient determined the degree of internal consistency of the questionnaire applied to validate the Circular Strategic Tool. Based on the results obtained after applying the three phases, it is concluded that the Circular Strategic Tool favored the users' decision making and reached the proposed objectives for the study.